Coaching livestock and fish projects on gender: Creating a body of knowledge around gender - Eerdewijk, Anouka van (International Livestock Research Institute, 2016)
Interview with Anouka van Eerdewijk (Royal Tropical Institute) for the book "A different kettle of fish? Gender integration in livestock and fish research". http://hdl.handle.net/10568/76684